Interleukin-1β has trophic effects in microglia and its release is mediated by P2X7R pore. Issue 1 (December 2016) - Monif, Mastura; Reid, Christopher; Powell, Kim; Drummond, Katherine; O'Brien, Terrence; Williams, David
Abstract Background Enhanced expression of the purinergic P2X7 receptor (P2X7R) occurs in several neuroinflammatory conditions where increased microglial activation is a co-existing feature. P2X7 receptors can function either as a cation channel or, upon continued stimulation, a large pore. P2X7R-over-expression alone is sufficient to drive microglial activation and proliferation in a process that is P2X7R pore dependent, although the biological signaling pathway through which this occurs remains unclear. Once activated, microglia are known to release a number of bioactive substances that include the proinflammatory cytokine interleukin-1β (IL-1β). Previous studies have linked P2X7R stimulation to the processing and release of IL-1β, but whether the channel or pore state of P2X7R is predominant in driving IL-1β release is unknown and is a major aim of this study. In addition, we will determine whether IL-1β has trophic effects on surrounding microglia. Methods Electron microscopy and immunohistochemistry were used to delineate the sub-cellular localization of P2X7R and IL-1β in primary hippocampal rat cultures. FM1-43 fluorescent dye and confocal microscopy were used to quantify vesicular exocytosis from microglia expressing the pore-forming P2X7R versus a non-pore-forming point mutant, P2X7RG345Y . IL-1β in culture was quantified with an enzyme-linked immunosorbent assay (ELISA). IL-1β intracellular processing was blocked with inhibition of caspase 1 (with a synthetic peptide antagonist), and its extracellular form was neutralized with an IL-1β neutralizing antibody. Microglial activation and proliferation was quantified immunohistochemically with confocal microscopy. Results P2X7R and IL-1β were co-localized in lysosomes. Vesicular exocytosis was higher in microglia expressing the pore-forming P2X7R compared to those expressing the non-pore-forming mutant. There was increased IL-1β in cultures expressing the pore-forming P2X7R, and this proinflammatory cytokine was found to mediate the trophic effects of P2X7R pore in microglia. Inhibition of IL-1β production and function resulted in a significant decrease in P2X7R-mediated microglial activation and proliferation. Conclusions IL-1β is a mediator of microglial activation and proliferation, and its release/production is P2X7R pore dependent. Blockade of P2X7R pore could serve as a therapeutic target in alleviating the degree of inflammation seen in neurodegenerative and neoplastic conditions.